Penguatan Etika dan Budaya Integritas Aparatur Negara: Upaya Meningkatkan Kepercayaan Publik terhadap Pelayanan Pemerintah - Didit Darmawan; Achmad Fatkhur Rokman; Nanda Devi Juniar; Yusrenicha Retna Ningsih; Nailul Ulah Al Chumairoh Machfud (LPPM STISIP IMAM BONJOL, 2026)
This study analyzes the relationship between the application of ethical values in public service and the integrity of state apparatus on the level of public trust. The study uses a qualitative approach through a literature review of various scholarly sources from the last two decades. The results of the study indicate that the application of ethical values such as justice, accountability, transparency, and professionalism can increase public trust in the government. Conversely, the low integrity of the state apparatus will hurt the quality of public service, encouraging the growth of corrupt practices, bureaucratic inefficiency, service discrimination, and the decline of the merit system and public trust. This study also describes various efforts that the government can undertake to build and strengthen a culture of integrity within the state apparatus, including: enforcement of regulations and strict sanctions, continuous ethics training, implementation of a merit system in recruitment and promotion, public involvement in oversight, and exemplary bureaucratic leadership. These findings confirm that strengthening a culture of integrity and ethics must be a top priority in the bureaucratic reform agenda to realize professional, clean, and trusted public services.